2020
DOI: 10.28991/cej-2020-03091480
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Identification for Representative Building Typologies: Three Case Studies from Bucharest Area

Abstract: The paper presents results from an experimental program implemented for three representative buildings in Bucharest metropolitan area and aimed to explore the potential of various dynamic identification methods in providing information about building state changes. The objective is to establish reference values of potential use in rapid earthquake damage detection systems. Each of the selected buildings was designed according to a different seismic code, in force at the time of its construction. The methods em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The second building, located in Magurele city, is the headquarters of the Institute of Atomic Physics (IAP). It is an office building retrofitted after the Vrancea 1977 earthquake and instrumented with three accelerometers installed in the basement (TURN1), sixth floor (TURN2), and 10th floor (TURN3; see Tiganescu et al, 2019Tiganescu et al, , 2020. The third instrumented building is Unirea Hotel in Focsani, where stations are deployed in the basement of the structure (FOCR1), the fourth floor (FOCR2), and the eighth floor (FOCR3).…”
Section: Stations In Buildings Used For Structural Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…The second building, located in Magurele city, is the headquarters of the Institute of Atomic Physics (IAP). It is an office building retrofitted after the Vrancea 1977 earthquake and instrumented with three accelerometers installed in the basement (TURN1), sixth floor (TURN2), and 10th floor (TURN3; see Tiganescu et al, 2019Tiganescu et al, , 2020. The third instrumented building is Unirea Hotel in Focsani, where stations are deployed in the basement of the structure (FOCR1), the fourth floor (FOCR2), and the eighth floor (FOCR3).…”
Section: Stations In Buildings Used For Structural Monitoringmentioning
confidence: 99%
“…Recent studies have shown a significant reduction of the noise level due to the restrictions imposed by authorities at local, regional, and national scales to prevent the spread of COVID-19. The noise reduction was noticed at stations located inside cities (e.g., Tokyo, Barcelona, Milano, Verona, Florence, Catania, Auckland, Querétaro; see Yabe et al, 2020;Diaz et al, 2021;Poli et al, 2020;Cannata et al, 2021;van Wijk et al, 2021;De Plaen et al, 2021), but it has also been reported at stations far from populated areas (e.g., the Black Forest; see Lecocq et al, 2020a). The observed drop in the seismic noise is not uniform, it varies from one place to another depending on the characteristics of the noise sources in the area and the way they were affected by the different societal responses to activity restrictions (Xiao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…e present research aimed to study how strain and loading manner would affect characteristics related seismic resistance of the under study plate panel. Experiments suggest how behavior of shear panels built with LYP steel changes under different loading speeds and incremental displacements [18].…”
Section: Seismic Characteristics Of Lyp Sswsmentioning
confidence: 99%
“…We live in a world in which the branding culture is obviously seen in all human behaviors and places [25]. City branding is an issue that governments pay special attention to it now.…”
Section: Introductionmentioning
confidence: 99%